Resource management in HPLC: Unveiling a green face of pharmaceutical analysis - Stojanović, Jevrem; Krmar, Jovana; Otašević, Biljana; Protić, Ana (Archives of Pharmacy, 2023)
High-pressure liquid chromatography (HPLC) is a technique of paramount importance in the analysis of pharmaceuticals because of its ability to separate moderately polar to less polar compounds, such as drugs and related substances. The concept of green analytical chemistry (GAC) aims to provide more environmentally friendly and safer analytical methods in terms of reagents, energy, and waste. One of the major challenges of GAC is to find an appropriate approach to evaluate the greenness of analytical methods. An extension of GAC, called white analytical chemistry (WAC), has been introduced to consider not only environmental friendliness, but also other aspects that contribute to the sustainability of methods, such as analytical and economic or practical efficiency. HPLC methods are intrinsically not green, due to the high consumption of toxic organic solvents and the resulting generation of large amounts of toxic waste. Fortunately, there are many approaches to overcome the non-green character of HPLC methods. In this article, various modifications of the HPLC methods that increase its environmental friendliness are presented, as well as the various tools used to evaluate environmental friendliness. In addition, the new concept of white analytical chemistry is presented.